Microperimetric evaluation of chronic central serous chorioretinopathy after half-dose photodynamic therapy - Fujita K (Dove Medical Press, 2012)
Kyoko Fujita,1 Kei Shinoda,1,2 Celso Soiti Matsumoto,2 Yutaka Imamura,3 Etsuko Tanaka,4 Yoshihiro Mizutani,1 Atsushi Mizota,2 Mitsuko Yuzawa11Department of Ophthalmology, Surugadai Nihon University Hospital, Tokyo, 2Teikyo University School of Medicine, University Hospital Itabashi, Tokyo, 3Teikyo University School of Medicine, University Hospital Mizonokuchi, Kanagawa, 4Kyorin University School of Medicine, Mitaka, JapanBackground: The purpose of this study was to determine baseline clinical factors to correlate the outcome of half-dose verteporfin photodynamic therapy (PDT) in eyes with chronic central serous chorioretinopathy (CSC).Methods: In this prospective, non-comparative, interventional case series, 14 eyes of 14 patients with chronic CSC who received half-dose verteporfin PDT were examined. The best-corrected visual acuity (BCVA), macular sensitivity in the central 4, 8, and 12 degrees, and fixation stability were evaluated at baseline and at months 1, 3, 6, and 12 after half-dose verteporfin PDT. Macular sensitivity and fixation stability were determined by MP-1 microperimetry.Results: Mean retinal sensitivity in the central 4 and 8 degrees was significantly better at 1, 3, 6, and 12 months after half-dose verteporfin PDT than at baseline. BCVA was significantly better after half-dose verteporfin PDT but only after 3 months. Fixation was relatively unstable in three eyes at baseline, but became stable at 12 months. BCVA at 12 months was significantly correlated with pre-PDT fixation stability (r = 0.7120, P = 0.0038).Conclusion: Half-dose verteporfin PDT results in a significant increase in mean central retinal sensitivity for at least 12 months. Our findings indicate that microperimetry is a useful method for evaluating the functional benefits of half-dose verteporfin PDT in eyes with chronic CSC.Keywords: microperimetry, fixation point, retinal sensitivity, photodynamic therapy, chronic central serous chorioretinopathy